2020
DOI: 10.1038/s41420-020-00371-2
|View full text |Cite
|
Sign up to set email alerts
|

The ZNF750–RAC1 axis as potential prognostic factor for breast cancer

Abstract: The human zinc finger (C2H2-type) protein ZNF750 is a transcription factor regulated by p63 that plays a critical role in epithelial tissues homoeostasis, as well as being involved in the pathogenesis of cancer. Indeed, missense mutations, truncation and genomic deletion have been found in oesophageal squamous cell carcinoma. In keeping, we showed that ZNF750 negatively regulates cell migration and invasion in breast cancer cells; in particular, ZNF750 binds and recruits KDM1A and HDAC1 on the LAMB3 and CTNNAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
(71 reference statements)
1
13
0
Order By: Relevance
“…Our observations have reported that resveratrol inhibited cell proliferation and induced apoptosis in CAL-27 cells by suppressing the expression of RAC1. In addition, ZNF750 overexpression also decreased the RAC1 expression, whereas its underexpression induced RAC1 level, which is consistent with previous investigation [16]. In our study, RAC1 agonist partially reversed the inhibitory effects of resveratrol on OSCC cell growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observations have reported that resveratrol inhibited cell proliferation and induced apoptosis in CAL-27 cells by suppressing the expression of RAC1. In addition, ZNF750 overexpression also decreased the RAC1 expression, whereas its underexpression induced RAC1 level, which is consistent with previous investigation [16]. In our study, RAC1 agonist partially reversed the inhibitory effects of resveratrol on OSCC cell growth.…”
Section: Discussionsupporting
confidence: 93%
“…When activated, RAC1 is involved in the cell migration, through a cytoskeleton rearrangement, and in cell survival [13][14][15]. Furthermore, ZNF750 represses the expression of RAC1 in breast cancer cell lines, by directly binding its promoter region [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, we still need to uncover specific biomarkers that can assist in diagnosis, prognosis and proper treatment for each patient [31,32]. We have recently shown the involvement of the p53 family [33][34][35][36][37][38] and in particular of p63 via the regulation of Sonic Hedgehog in the control of breast cancer proliferation [39][40][41][42][43][44], its transcriptional target ZNF750 [45,46], as well as p73 [47]. These molecular mechanisms also showed the involvement of long noncoding RNA uc.63 [48].…”
Section: Breast Cancers and Metabolic Reprogrammingmentioning
confidence: 99%
“…A low expression level of ZNF750 correlates with a higher incidence of undifferentiated histology and is associated with malignant progression and poor prognosis in SCC patients. We have recently reported that ZNF750 inhibits the migratory and invasive properties of breast cancer cells by recruiting the epigenetic platform KDM1A/HDAC1 to the genetic loci of LAMB3 and CTNNAL1, ultimately repressing their expression [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%